2017
DOI: 10.15516/cje.v19i1.2313
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Use of Educational Software in Teaching Biology /Učinkovitost primjene edukativnih računalnih programa u nastavi biologije

Abstract: The paper analyzes comparative effectiveness of the use of educational software and traditional teaching methods in biology instruction for high school students. A random sample consisted of 173 students of grade 12 of a high school in Zrenjanin, Serbia, who were randomly distributed into the control and experimental groups. The students in the experimental group learned biology content (Mechanisms of Heredity) using educational software, whereas the students in the control group learned the same content using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Also, other authors confirmed that the application of computers and various multimedia materials such as computer presentations, entertainment, educational software and e-textbooks in the classroom contributes to increased efficiency compared to traditional teaching in subjects such as Nature and society (Cvjetićanin, Pećanac, Sakač, & Djurendić-Brenesel, 2013) and biology (Cheng, Cheng, & Chen, 2012;Nwafor & Charity, 2013;Rotbain et al, 2008;Odadžić et al, 2017;Singh, 2010;Yusuf, & Afolabi, 2010;Županec et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Also, other authors confirmed that the application of computers and various multimedia materials such as computer presentations, entertainment, educational software and e-textbooks in the classroom contributes to increased efficiency compared to traditional teaching in subjects such as Nature and society (Cvjetićanin, Pećanac, Sakač, & Djurendić-Brenesel, 2013) and biology (Cheng, Cheng, & Chen, 2012;Nwafor & Charity, 2013;Rotbain et al, 2008;Odadžić et al, 2017;Singh, 2010;Yusuf, & Afolabi, 2010;Županec et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…They enable a new organization of the teaching process, which is appropriate to individual abilities and interests of students. Numerous studies have shown that the application of computers in teaching most of the subjects increases its effectiveness: in teaching geography (Ivkov-Džigurski, Ivanović, & Pešić, 2009), mathematics (Laketa, Drakulić, Đurović, & Likić, 2013), foreign languages (Mirzayantz Đukić, 2011) and biology (Odadžić, Miljanović, Mandić, Pribićević, & Županec, 2017). According to Danilović, computers have stimulated the development of the teaching process in the fields of simulation of learning circumstances, automation of the sources and means of providing feedback, assistance in the preparation and evaluation of teaching materials, integration of the teaching media (film, video clips, TV and text) both in the group and individual teaching (Danilović, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future Direction: Promote inclusive teaching practices, provide professional development on diversity and inclusion, and advocate for resources to support diverse learners (Odadžić et al 2017).…”
Section: ) Engagement and Relevancementioning
confidence: 99%